PERSEPSI MAHASISWA TENTANG PENGGUNAAN APLIKASI TURNITIN UNTUK MENCEGAH TINDAK PLAGIARISME DI PERPUSTAKAAN UNIVERSITAS BINA DARMA PALEMBANG - Devi Sagita Putri; Budhi Santoso (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2020)
This research aims to determine the perseptions of 2015-2016 class students about the use of the Turnitin aplication to prevent plagiarism in the Library Universitas Bina Darma Palembang and to find out what aspect need to be improved. The type of research used is descriptive with a quantitative approach. The sample in this research were 365 respondents. The main data collections method is a questionnaire with a Likert Scale. Test the validity of the instrument using the Product Moment, while the realibility test used Cronbach Alpha, with calculations using SPSS 22.0 For Windows. The analysis data in this research used the Mean and Grand Mean formula. The result of the research be conclude that perseptions of 2015-2016 class students about the use of the Turnitin aplications to prevent plagiarism in the Bina Darma University Library in Palembang is a “Very High” category with a total average value of (4,20), and are at interval 4,20-5,0. While the aspect that must be improved is the aspect of affection (attitude), with the lowest average score (4,14) compared to other aspects.